Field distribution of banana weevil (Cosmopolites sordidus (Germar) adults in cooking banana stands in Uganda - Gold, Cliford S.; Night, G.; Ragama, P.E.; Kagezi, G.H.; Tinzaara, William; Abera, A.M. (Springer, 2004)
The banana weevil, Cosmopolites sordidus (Germar), is a nocturnal insect that is not readily observed in banana fields. Knowledge on its distribution is essential for the design of management strategies that target the adult stage. Marked weevils were released into seven-year-old banana plots. Ten days later the plots were systematically sampled for adult weevils by first removing the banana leaf mulch and residues, searching subsections of the soil to depths of 3 and 25 cm and, finally, removal and dissection of the banana mats. Of the marked weevils, 62, 56 and 82% respectively, were recovered in three trials. Most weevils were found in close association with either the banana mat (46–66%) or with cut residues lying on the ground between the mats (24–31%). Lesser numbers were found in the leaf mulch and in the top 3 cm of soil away from the mat. The distribution of weevils is likely to be influenced by crop management practices and the availability of residues and by the presence of mulch. Implications for banana weevil IPM are discussed.